A seminar notes for school teachers on cardiopulmonary resuscitation (CPR) and automated external defibrillation (AED) - Nurumal, Mohd Said; Che Hasan, Muhammad Kamil; Jamaludin, Sumaiyah @ ThandarSoe; Aung, Khin Thandar; Mohd Nor, Mahirah; Mat Hussain, Maryam Farah Nadia (2021)
Studies have shown that 88% of cardiac arrests occur at home. Cardiac arrest can be happened to anyone, anytime, anywhere even without warning to people who appear healthy. The person’s life you save could be a loved one. Furthermore, statistics show that the earlier CPR is initiated, the greater the chances of survival. Thus, this knowledge transfer program aimed to provide the knowledge on how to perform the CPR and how to use the AED in OHCA by the bystanders